2017
DOI: 10.1111/sum.12348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use and tillage depth on dynamics of soil microbial properties, soil carbon fractions and crop yield after conversion of short‐rotation coppices

Abstract: The effect of conversion of short-rotation coppices (SRCs) to agricultural land on soil organic carbon (SOC), soil microbial properties and crop yield is largely unknown. The objective of this study was to assess the effects of subsequent land use and tillage depth after conversion of SRCs on (i) total SOC (ii) soil C fractions with differentiation of total harvest residues and woody harvest residues from SRC and maize by 13 C analysis and (iii) dry matter and N yield of grassland and maize. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…This is in agreement with previous findings that the C/N ratio of residues does not regulate the residue decomposition in the soil, but mineralization depends more on the biochemical quality of the residues [46]. Toenshoff et al [25] reported a value of C mineralization of PBO and FR of poplar residues of about 20% and 25% of added C after 30 and 42 days of incubation, while Wachendorf et al [47] showed that decomposition of woody harvest is rapid.…”
Section: Modeling C and N Mineralization Of Bgb Decomposition In The ...supporting
confidence: 90%
See 1 more Smart Citation
“…This is in agreement with previous findings that the C/N ratio of residues does not regulate the residue decomposition in the soil, but mineralization depends more on the biochemical quality of the residues [46]. Toenshoff et al [25] reported a value of C mineralization of PBO and FR of poplar residues of about 20% and 25% of added C after 30 and 42 days of incubation, while Wachendorf et al [47] showed that decomposition of woody harvest is rapid.…”
Section: Modeling C and N Mineralization Of Bgb Decomposition In The ...supporting
confidence: 90%
“…Miscanthus FR had the lowest C mineralization and lowest values of k DEOM (Figure 4). Amounts of FR C mineralization were comparable with values of about 10% of added C measured by Wachendorf et al [47] and values in the range of 7-13% found by other authors [52,53]. More likely, C mineralization of FR was lower than PBO, due to the different biochemical quality, resulting in different accessibility of degradable C compounds to microbes [39,54,55].…”
Section: Modeling C and N Mineralization Of Bgb Decomposition In The ...supporting
confidence: 87%
“…There are concerns that at the end of the PEC cultivation cycle, the conversion of these crops back to arable land could negatively affect the SOC stock. However, a positive effect of conversion on SOC is possible, due to the high amount of crop residues entering to the soil as new particulate organic matter (POM) with the disruption of BGB during the re‐conversion process (Toenshoff, Georg, et al, 2013; Toenshoff, Stuelpnagel, et al, 2013; Wachendorf et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The depth to the fragipan layer in ranges between 0.1 m and 2.0 m below the surface. In most locations, the fragipan layer is below historical tillage depths, typically 30 cm, and is therefore intact [34][35][36]. Furthermore, no-till practices are currently practiced throughout the watershed to prevent additional disturbances to the fragipan layer.…”
Section: Study Areamentioning
confidence: 99%